Corporate governance, finance, and global strategy - Bozos, Konstantinos; Filatotchev, Igor; Goergen, Marc (Elsevier, 2025)
We bring together insights from international business (IB), finance, economics, and accounting to offer a multi-faceted perspective on firm strategies and global governance. Complex, multi-level institutional environments—particularly in emerging markets—necessitate cross-fertilisation between IB and other disciplines. Research on the role of foreign investors in both corporate financing and internationalisation is associated with persistent gaps and research opportunities, especially in understanding how state-owned enterprises and sovereign wealth funds navigate regulatory and governance challenges. Evolving management accounting practices require that traditional frameworks be adapted to better accommodate multi-national contexts. Further, the latest developments in research on capital structure and financial constraints suggest that they act as both barriers and enablers for international expansion. Finally, contemporary challenges, such as populism, climate risk, and digital disruption, underscore the pressing need for interdisciplinary research with purpose and broad scope. We recommend an integrated research agenda that reconciles these diverse elements to advance both theory and practice in global business.
Keywords: 53 Ciencias Económicas; ODS 9 - Industria, innovación e infraestructura; ODS 13 - Acción por el clima; ODS 17 - Alianzas para lograr los objetivos; Global strategy; Corporate governance; Finance; Economics